A pragmatic analysis of public signs in China - Deng, Jing (Linguistica Atlantica, 2014)
This paper investigates the linguistic and pragmatic features of public signs in three distinct historical stages of the Chinese society. It then focuses on the new features of public signs, in order to shed light on the characteristics of public language and social life in modern China.